ANALISIS PENGARUH LABA BERSIH, ARUS KAS OPERASI, PEMBAYARAN DIVIDEN KAS SEBELUMNYA, DAN QUICK RATIO TERHADAP DIVIDEN KAS PADA PERUSAHAAN LQ-45 YANG TERDAFTAR DI BURSA EFEK INDONESIA PERIODE 2011-2013 - Tiocandra, Riyondi; -, Kamaliah; Idrus, Rahmiati (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2015)
The objective of this research is to examine and analyze the influence of the net income, operating cash flow, previous cash dividend payment, and quick ratio toward cash dividend at the LQ-45 corporations listed in the Indonesia Stock Exchange 2011-2013. The Population in this research are LQ-45 corporations which are listed at the Stock Exchange during 2011-2013. Based on purposive sampling method obtained that the 22 companies which are used as the samples in this research. The examination is conducted using multiple linear regression method of processing data with SPSS version 17. The results showed that the variables of net income and previous cash dividend payment have a significant influence toward cash dividend, while the independent variables operating cash flow and quick ratio have no significant influence toward cash dividend.Keywords: Net Income, Cash, Dividend Payment, and Quick Ratio